The impact of atmospheric aerosol particles on the brightness of the night sky. (October 2020) - Ściężor, Tomasz; Czaplicka, Anna
Highlights: Aerosols are the main light scattering factor in the cloudless sky. Particulate matter (PM) plays a special role in the sky glow over the residential areas. There is a linear relationship between PM concentration and brightness of the sky glow. Particulate matter accumulates at the boundaries of atmospheric layers. Desert dust seasonally plays a special role in the sky glow over the protected areas. Abstract: This paper analyses the impact of various types of aerosols, both of natural and anthropogenic origin, on the brightness of the night sky glow in southern Poland. The particles of particulate matter, related to the combustion of solid fuels in the winter, the volcanic or desert dust, as well as mists and haze, are considered as the artificial light scattering sources. Measurements of the brightness of the cloudless and moonless night sky were done in 2009–2016, both within the city of Krakow and in suburban areas, as well as in mountainous ones. The strong linear correlation between the brightness of such sky and the concentration of particulate matter is shown. The acoustic sounding of the atmosphere (SODAR) has indicated the possibility of a relationship between the brightness of the night sky and the amount of such particulates, which accumulate in atmospheric boundary layers. The usefulness of the theoretical model of horizontal transport of dust in the atmosphere (FAPPS) for forecasting the brightness of the night sky glow is also pointed out. A clear effect of the Saharan origin dust clouds on the brightness of the night sky glow is shown. This brightness, in the conditions of a low level of light pollution, is associated with the forecasted optical density of such clouds. It is also demonstrated, that with the thickening of mist, the impact of distant light sources on the brightness of the night sky decreases, but the one of a nearby sources becomes more significant. The conclusion states that anthropogenic particulate matter has the greatest impact on the brightness of the cloudless night sky glow in winter. In areas heavily polluted with light, fogs and mist are particularly important. In areas with low levels of light pollution, the clear impact of desert dust is visible.